Shariah Issues of Ownership and Possession of Asset-Based Sukuk Structure: A Shariah Scholars’ Perspective - AbdulKareem, Ibraheem Alani; Mahmud, Mohd Sadad (UUM Press, 2024)
Sukuk serves as an instrument in the global Islamic financial market, which has experienced expansion in recent years. Despite this notable growth, Sukuk encounters Shariah-related concerns pertaining to the possession of underlying assets. This study investigates the Shariah perspective on Sukuk investors without full ownership or possession of the underlying asset under asset-based Sukuk. This study adopted a qualitative method and used primary and secondary data sources. Primary data was gathered from eight participants through semi- structured interviews with Shariah experts in Malaysia and Nigeria. NVivo 10 was used the analyse the data thematically. This study used relevant resources such as respected journals, textbooks, newspapers, and other relevant sources for secondary data. Our findings show that the Sukuk holders must take possession of underlying assets during the duration of the project. Therefore, it is illegal for a person to sell assets that he or she does not own. A complete ownership transfer must occur, allowing Sukuk investors to lease the asset back to the government or issuer. The findings also reveal that the legal system of the country where the Sukuk was issued is one of the factors that restricts investors from receiving the underlying asset of Sukuk, particularly in asset-based Sukuk. The study’s consequences include that the stakeholder’s issue is Sukuk under Shariah legislation, attracting investors to participate in Shariah-compliant investments. Moreover, it is recommended that investors use underlying assets during Sukuk projects to avoid gharar.